Publisher Correction: Targeting hepatic glutaminase activity to ameliorate hyperglycemia - Miller, Russell A.; Shi, Yuji; Lu, Wenyun; Pirman, David A.; Jatkar, Aditi; Blatnik, Matthew; Wu, Hong; Cárdenas, César; Wan, Min; Foskett, J. Kevin; Park, Junyoung O.; Zhang, Yiyi; et al. (Nature medicine, 2018)
In the version of this article initially published, the “[13C2]α-ketoglutarate” label on Fig. 1g is incorrect. It should be “[13C5]α-ketoglutarate”. Additionally, in Fig. 3b, the “AAV-GFP” group is missing a notation for significance, and in Fig. 3c, the “AAV-GLS2-sh” group is missing a notation for significance. There should be a double asterisk notating significance in both panels. Finally, in the Fig. 4g legend, “[13C6]UDP-glucose” should be “[13C3]UDP-glucose”, and in the Fig. 4h legend, “[13C6]hexose” should be “[13C3]hexose”. The errors have been corrected in the HTML and PDF versions of this article.